Epidemiology of neuropathic pain: an analysis of prevalence and associated factors in UK Biobank. (10th March 2023) - Baskozos, Georgios; Hébert, Harry L.; Pascal, Mathilde M.V.; Themistocleous, Andreas C.; Macfarlane, Gary J.; Wynick, David; Bennett, David L.H.; Smith, Blair H.
Abstract : Supplemental Digital Content is Available in the Text. An analysis of UK Biobank participants who completed a detailed pain questionnaire identified factors associated with neuropathic pain (NeuP) vs no chronic pain and non-NeuP and estimated the prevalence of NeuP. Abstract: Introduction: Previous epidemiological studies of neuropathic pain have reported a range of prevalences and factors associated with the disorder. Objectives: This study aimed to verify these characteristics in a large UK cohort. Methods: A cross-sectional analysis was conducted of 148, 828 UK Biobank participants who completed a detailed questionnaire on chronic pain. The Douleur Neuropathique en Quatre Questions (DN4) was used to distinguish between neuropathic pain (NeuP) and non-neuropathic pain (non-NeuP) in participants with pain of at least 3 months' duration. Participants were also identified with less than 3 months' pain or without pain (NoCP). Multivariable regression was used to identify factors associated with NeuP compared with non-NeuP and NoCP, respectively. Results: Chronic pain was present in 76, 095 participants (51.1%). The overall prevalence of NeuP was 9.2%. Neuropathic pain was significantly associated with worse health-related quality of life, having a manual or personal service type occupation, and younger age compared with NoCP. As expected, NeuP was associated with diabetes and neuropathy, but also other pains (pelvic, postsurgical, and migraine) and musculoskeletal disorders (rheumatoid arthritis, osteoarthritis, and fibromyalgia). In addition, NeuP was associated with pain in the limbs and greater pain intensity and higher body mass index compared with non-NeuP. Female sex was associated with NeuP when compared with NoCP, whereas male sex was associated with NeuP when compared with non-NeuP. Conclusion: This is the largest epidemiological study of neuropathic pain to date. The results confirm that the disorder is common in a population of middle- to older-aged people with mixed aetiologies and is associated with a higher health impact than non-neuropathic pain.